Evaluating the role of a trypsin inhibitor from soap nut (Sapindus trifoliatus L. Var. Emarginatus) seeds against larval gut proteases, its purification and characterization. Issue 1 (December 2015) - Gandreddi, V; Kappala, Vijaya; Zaveri, Kunal; Patnala, Kiranmayi
Abstract Background The defensive capacities of plant protease Inhibitors (PI) rely on inhibition of proteases in insect guts or those secreted by microorganisms; and also prevent uncontrolled proteolysis and offer protection against proteolytic enzymes of pathogens. Methods An array of chromatographic techniques were employed for purification, homogeneity was assessed by electrophoresis. Specificity, Ki value, nature of inhibition, complex formation was carried out by standard protocols. Action of SNTI on insect gut proteases was computationally evaluated by modeling the proteins by threading and docking studies by piper using Schrodinger tools. Results We have isolated and purified Soap Nut Trypsin Inhibitor (SNTI) by acetone fractionation, ammonium sulphate precipitation, ion exchange and gel permeation chromatography. The purified inhibitor was homogeneous by both gel filtration and polyacrylamide gel electrophoresis (PAGE). SNTI exhibited a molecular weight of 29 kDa on SDS-PAGE, gel filtration and was negative to Periodic Acid Schiff's stain. SNTI inhibited trypsin and pronase of serine class. SNTI demonstrated non-competitive inhibition with a Ki value of 0.75 ± 0.05×10-10 M. The monoheaded inhibitor formed a stable complex in 1:1 molar ratio. Action of SNTI was computationally evaluated on larval gut proteases fromHelicoverpa armigera andSpodoptera frugiperda . SNTI and larval gut proteases were modeled and docked using Schrodinger software. Docking studies revealed strong hydrogen bond interactions between Lys10 and Pro71, Lys299 and Met80 and Van Der Waals interactions between Leu11 and Cys76amino acid residues of SNTI and protease fromH. Armigera . Strong hydrogen bonds were observed between SNTI and protease ofS. frugiperda at positions Thr79 and Arg80, Asp90 and Gly73, Asp2 and Gly160 respectively. Conclusion We conclude that SNTI potentially inhibits larval gut proteases of insects and the kinetics exhibited by the protease inhibitor further substantiates its efficacy against serine proteases.